REFORMS IN THE FIELD OF EDUCATION AT A NEW STAGE OF DEVELOPMENT - Yuldashev Serobjon Urmonaliyevich; Komilova Sevinch Akmaljon kizi (Modern American Journals, 2025)
The article examines the issues of deepening ongoing reforms in the field of education, organizing the activities of educational institutions based on advanced international experience, improving the system of teacher training, and supporting the activities of non-state educational organizations. It also analyzes measures aimed at enhancing human resource potential in education, organizing educational processes and service delivery in educational institutions based on new principles, bringing the quality of educational services up to international standards, and accelerating the pace of reforms.
Keywords: Modernization, state scholarships, information analysis, digital government, hemis, electronic library, diplom.edu.uz, researcher.